Asymptomatic giant mediastinal mass: a rare case of thymolipoma - Mourad,Omar Moté Abou (2009)
Thymolipoma is a very rare benign neoplasm of the thymus. We present the case of a 42-year-old male with a massive mediastinal tumor discovered on a chest X-ray after a motorcycle accident. The patient had no complaints, and his physical examination was unremarkable. Chest CT scans revealed a lipomatous mass containing areas of soft tissue density. The patient was submitted to median sternotomy expanded to left anterolateral thoracotomy, resulting in the complete excision of the tumor. The pathological diagnosis was thymolipoma. Thymolipoma usually attains enormous dimensions by the time of diagnosis, and the occasional symptoms are related to compression of adjacent structures. Surgical resection is the treatment of choice and offers the only possibility of cure. The airway deserves special care during anesthesia induction.